Readiness of future teachers to work at school: Review of theoretical and empirical research - L. A. Novopashina; E. G. Grigorieva; N. F. Ilyina; I. А. Bidus (Russian State Vocational Pedagogical University, 2024)
Introduction. The current review article studies and systematises modern knowledge about the readiness of future teachers to work at school. The relevance of the study is due to the unwillingness of graduates of pedagogical universities to work in their speciality, the departure of novice teachers from the profession, and the increase in the number of open vacancies. The speed of ongoing changes, information and technological progress, the need to carry out online education and use artificial intelligence make it necessary to systematise the results of modern research. A review of various scientific fields allows us to take a step towards interdisciplinarity and describe different points of view in theoretical and empirical research. Moreover, it is important to answer the question of the representation of concepts and models of readiness, as well as to investigate the areas of further research directions.Aim. The present research aims to review and systematise international and Russian theoretical and empirical studies on the readiness of future teachers to work at school.Methodology and research methods. The methodology of the study was a descriptive (semi-systematic) approach to the review of theoretical and empirical studies. The search strategy consisted of the following stages: (1) identification of research questions; (2) search for relevant studies; (3) selection and exclusion for analysis; (4) data comparison; (5) generalisation and presentation. The methods of systematic search, comparative and content analysis were employed. The search for English-language publications was conducted in World Scientific, Scopus and Elsevier (ScienceDirect), which are in open access (open access&open archive). A total of 531 sources were identified. Then, by the Prisma method, 119 articles were selected, with a search depth from 2016 to 2023. The analysis of Russian-language articles was carried out in the scientific electronic library eLIBRARY.RU. A set of words "readiness&future teachers&work at school" was used for the search; as a result, 120 sources were obtained. The selected articles were analysed from the point of view of concepts, directions, models and factors of readiness for professional pedagogical activity and work at school.Results. The number of studies on this topic has been growing since 2008, with the highest values observed in 2016 and 2020. In 54.6 % of publications, theoretical models are considered. It is revealed that the concept of "readiness" of a graduate of a pedagogical university/college or already a teacher to work at school significantly depends on the field of scientific knowledge within which this term is considered. The thematic mismatch of Russian and foreign studies has been established. 39.7 % of Russian studies are devoted to professional competencies, and every fourth foreign article (25.7 %) focuses on educational outcomes. The most frequent methods of data collection in empirical studies are interviews, surveys and experiments. External and internal factors of readiness are revealed. External ones are the content of the educational programme at a pedagogical university or college, the duration of training and the conditions for passing pedagogical practice. Internal factors include the choice of specialisation in accordance with individual preferences, knowledge of pedagogical support resources and modern teaching technologies, options, and features of the school context.Scientific novelty. For the first time, a systematic review of international and Russian studies on this topic has been conducted. A unique contribution to the field of research is the resulting database of publications in this area, which is publicly available for researchers and other interested parties (certificate of state registration of the database № 2023622782). The results obtained make it possible to develop a comprehensive interdisciplinary model of future teachers' readiness to work at school, considering all the changes and challenges of an information and technologically advanced society.Practical significance is due to the possibility of using the results obtained in the development of educational programmes in pedagogical training. Based on the data obtained, future researchers and teachers can conduct a meta-analysis, qualitative and quantitative assessment of readiness for professional pedagogical activity. The research outcomes make it possible to conduct further research and evaluate the author's readiness models for completeness, adequacy, and validity.